2020
DOI: 10.1186/s12890-020-1109-y
|View full text |Cite
|
Sign up to set email alerts
|

The rat model of COPD skeletal muscle dysfunction induced by progressive cigarette smoke exposure: a pilot study

Abstract: Background: Chronic obstructive pulmonary disease (COPD) skeletal muscle dysfunction is a prevalent malady that significantly affects patients' prognosis and quality of life. Although the study of this disease has attracted considerable attention, a definite animal model is yet to be established. This study investigates whether smoke exposure could lead to the development of a COPD skeletal muscle dysfunction model in rats. Methods: Sprague Dawley rats were randomly divided into model (MG, n = 8) and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“… 42 Another group reported that 16-week exposure of male Sprague-Dawley rats to cigarette smoke leads to less contractility of tibialis anterior muscles and a reduced cross-sectional area of gastrocnemius muscles, as well as emphysematous changes in the lung, elevated inflammatory factors in the serum, and ubiquitin protease induction in muscle tissue. 43 Additionally, in the present study, we showed a reduction in muscle mass and sMyHC-positive fibers in the smoke-exposed mice. Considering these data, rodents exposed to cigarette smoke for several months represent a well-established model for sarcopenia with COPD.…”
Section: Discussionsupporting
confidence: 70%
“… 42 Another group reported that 16-week exposure of male Sprague-Dawley rats to cigarette smoke leads to less contractility of tibialis anterior muscles and a reduced cross-sectional area of gastrocnemius muscles, as well as emphysematous changes in the lung, elevated inflammatory factors in the serum, and ubiquitin protease induction in muscle tissue. 43 Additionally, in the present study, we showed a reduction in muscle mass and sMyHC-positive fibers in the smoke-exposed mice. Considering these data, rodents exposed to cigarette smoke for several months represent a well-established model for sarcopenia with COPD.…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with previous studies showing MuRF-1 up-regulation in the skeletal muscles of CSexposed animals, CS exposure tended to increase MuRF-1 in WT mice (Figure 6). 11,39,40 Additionally, the markedly enhanced MuRF-1 protein levels in CS-exposed Parkin À/À mice further support the notion that Parkin plays a pivotal role in negatively regulating MuRF-1 protein levels in muscles during CS exposure. The participation of MuRF-1 in the process of MHC degradation was confirmed through MuRF-1 knockdown experiments, which showed significant recovery from CSE-induced MHC reduction in the myotubes (Figure 4).…”
Section: Discussionsupporting
confidence: 66%
“…Chronic obstructive pulmonary disease (COPD) is a chronic, debilitating disease, predominantly induced by air pollution and aging (Su et al, 2020). It is a major cause of chronic morbidity and the third leading cause of death globally (World Health Organization, 2018).…”
mentioning
confidence: 99%